Recombinant expression, in vitro refolding and characterizing disulfide bonds of a mouse inhibitory C-type lectin-like receptor Nkrp1b - Hernychová, L; Mrázek, H; Ivanova, L; Kukačka, Z; Chmelík, J; Novák, P (Physiological research, 2015)
As a part of the innate immunity, NK (Natural Killer) cells provide an early immune response to different stimuli, e.g. viral infections and tumor growths. However, their functions are more complex; they play an important role in reproduction, alloimmunity, autoimmunity and allergic diseases. NK cell activities require an intricate system of regulation that is ensured by many different receptors on a cell surface which integrate signals from interacting cells and soluble factors. One way to understand NK cell biology is through the structure of NK receptors, which can reveal ligand binding conditions. We present a modified protocol for recombinant expression in Escherichia coli and in vitro refolding of the ligand-binding domain of the inhibitory Nkrp1b (SJL/J) protein. Nkrp1b identity and folding was confirmed using mass spectrometry (accurate mass of the intact protein and evaluation of disulfide bonds) and one-dimensional nuclear magnetic resonance spectroscopy. The intention is to provide the basis for conducting structural studies of the inhibitory Nkrp1b protein, since only the activating Nkrp1a receptor structure is known.
Keywords: Animals; Protein Refolding; Escherichia coli; disulfidy; lektinové receptory NK-buněk - podrodina B; sekvence aminokyselin; Molecular Sequence Data; rekombinantní proteiny; Recombinant Proteins; Mice; buněčná inkluze; Amino Acid Sequence; myši; hmotnostní spektrometrie; Inclusion Bodies; magnetická rezonanční spektroskopie; molekulární sekvence - údaje; refolding proteinů; Mass Spectrometry; zvířata; Magnetic Resonance Spectroscopy; Disulfides; NK Cell Lectin-Like Receptor Subfamily B